Pengaruh Penggunaan E-Wallet, Teman Sebaya, dan Literasi Keuangan terhadap Perilaku Keuangan Mahasiswa Universitas 17 Agustus 1945 Surabaya melalui Kontrol Diri dan Perilaku Konsumtif - Maulana Ikhrom Ababil; Hwihanus, Hwihanus (Journal of Economics, Management, and Accounting, 2026)
The development of financial technology has driven significant changes in the financial behavior of students, particularly through the increasingly widespread use of e-wallets. On the other hand, students are also influenced by social factors such as peers and their level of financial literacy. This study aims to analyze the influence of e-wallet use, peers, and financial literacy on the financial behavior of students at Universitas 17 Agustus 1945 Surabaya, with self-control and consumptive behavior as mediating variables. This study uses a quantitative approach with a survey method. Data were collected through a Likert scale-based questionnaire and analyzed using Structural Equation Modeling (SEM). The results of this study are expected to provide a comprehensive picture of the factors that influence student financial behavior and the role of self-control and consumptive behavior in shaping that behavior. The findings of this study are expected to serve as a basis for educational institutions in designing programs to improve student financial literacy.